Towards a Low-carbon Economic Sustainable Development: Scenarios and Policies for Kazakhstan - Saimova, Sholpan; Makenova, Gulsim; Skakova, Aizhan; Moldagaliyeva, Aitolkyn; Beisembinova, Ardak; Berdiyarova, Zhamilya; Imanbekova, Bagdagul (International Journal of Energy Economics and Policy, 2020)
This paper analyses analysis current and future dependence of agriculture, industry, oil and gas sector on water supply in Kazakhstan under varying socioeconomic and climate change scenarios. To conduct the scenarios analysis, a multiple linear model was used; the model has been widely used to examine complex water systems in the water resource planning sector all around the world. The paper results show that by 2050 total water demand under normal weather conditions could increase from 20188.62 m3 in 2015 to 23010.18 m3 under sustainable use (SU) scenario, to 26794.85 m3 under current trends (CT) baseline scenario, and up to 30220.46 m3 under the more resource intensive (MRI) scenario, however, the future water demand may be affected by environmental changes. The largest change (relative to the CT scenario) in total demand of 32413.18 m3 would result from the combined effect of the temperature increase and decrease in precipitation. More than 55% of this change would be in agriculture sector. Through exploring water scenarios, this paper could assist Kazakhstani resource managers and policymakers in designing more effective eco-environment management plans and strategies in the face of climate change. Keywords: resources use; sustainable development; economic growth, Kazakhstan JEL Classifications: Q43, O47 DOI: https://doi.org/10.32479/ijeep.9604